Tolerância a estresses abióticos em sementes de Erythrina velutina Willd, (Leguminosae - Papilionoideae) nativa da caatinga - Reis, Renata Conduru Ribeiro (2012)
Mulungu (Erythrina velutina Willd.) tree belongs to the family Leguminosae and shows high potential to family farming uses, medicinal and economic for northeast region of Brazil. However, the knowledge about the behavior of their seeds under stress condition is scarce. The objective of this study is to characterize the physiological and metabolic profiles of germination and to determine the activity of antioxidant enzymes in seeds and seedlings under conditions of heat, water and salt stress. Were assessed the percentage, average time, average speed, index of speed and coefficient of uniformity of germination, size and fresh and dry weight of seedlings. Cotyledons, embryonic axis, shoot, root, and cotyledons of quiescent seeds were collected and after extraction was subjected to measurements of total soluble sugars (TSS), reducing sugars (RS), soluble protein (TP), total amino acids (AA), proline and activities of catalase (CAT), ascorbate peroxidase (APX), guaiacol peroxidase (GOPX) and glutathione S-transferase (GST). The germination, mobilization and degradation of reserves of E. velutina seeds were affected by low and high temperatures of incubation and also water restriction. Seed germination was not affected negatively by EC 18 dS.m-1, however water restriction promoted by NaCl solutions affected the growth of seedlings. Antioxidants activity varied depending on kind and level of applied stress, giving indications that germination might be slightly affected due to significant activity of antioxidant enzymes involved in defense against reactive oxygen species under conditions of abiotic stress.